Sepsis under pressure, intraoperative surgical site infection prevention practices among nurses in emergency surgical settings: A qualitative study - Racheal Nyarko; Eric Tornu; Gwendolyn Patience Mensah (PLoS ONE, 2026)
Background Surgical site infections are among the most common and preventable healthcare-associated infections globally. Nurses play a pivotal role in implementing preventive measures for surgical site infections. This study examined intraoperative surgical site infection prevention measures and their outcomes among nurses managing emergency surgeries at a tertiary hospital in Ghana. Methods A qualitative exploratory descriptive design was employed. Nineteen nurses with at least three years of experience in the operating theatre were purposively selected from the surgical directorate of a teaching hospital in the Ashanti region of Ghana. Data were collected through semi-structured face-to-face individual interviews and analyzed thematically using Braun and Clarke’s approach. Findings The two themes and eight subthemes generated revealed that the structures influencing surgical site infection prevention encompassed the physical layout of the theatre, availability of equipment and materials, monitoring and supervision, institutional protocols, communication and teamwork and preoperative skin preparation. Furthermore, the outcomes of nursing interventions included improved wound healing and enhanced job satisfaction. However, resource limitations and inconsistent supervision posed barriers to optimal care. Nurses expressed fulfilment when wound healing progressed well, while infections led to emotional distress and increased workload. Conclusion Intraoperative infection prevention practices, when supported by strong institutional structures can significantly reduce surgical site infections and enhance patient outcomes. Investing in nurse-led infection control capacity, resource availability, and supportive supervision is essential for improving surgical safety in emergency contexts.